Stabilisasi inflasi melalui pengelolaan nilai tukar: Studi literatur tentang pengalaman reformasi ekonomi Argentina - Dadi Krismatono (Economic Journal of Emerging Markets, 1998)
This plain paperwork was intended to describe the experience of Argentina which had held its economic reform during 1991-1994. In April 1991 Argentina embarked on a far-reaching program of economic reform designed to bring inflation down to acceptable basis.